Synthesis and Use of Environmentally Friendly Superabsorbent Smart Polymer to Improve the Properties of the Gypsum Soil - Foud Nihad Abed; Mustafa Mahdi Abdulridha; A. A. Hamad Mohamad; Zelalem Meraf; Mohamed Abdelhedi (Adsorption Science & Technology)
A smart, environmentally friendly superabsorbent polymer was prepared using solvents. It was polymerization on the microwave rays at a medium capacity and for 25 minutes, where the yellow gel was obtained. The polymer was cut and washed with absolute ethanol and methanol and was dried at a temperature of 60°C. Then, the polymer was extracted and milled with ceramic fat until obtaining a very soft powder, and the tests were taken as a formula for a scanning electron microscope and infrared spectrum. The results showed that the absorption value of polymer is at the equivalent acid function, where the absorption capacity was 467.32 grams. At room temperature, the water retention rate was 71%, and at 50°C, it was 52%, and the gel content was 90%. The results showed an improvement in the properties of the gypsum soil in terms of virtual density, porous, and acidic function, reaching 7.3%. The proportion of significant elements (P, N, Ca, K, Na) and moisture content in the soil was 64%, the cumulative tip amount and the consistency of soil granules through wet and dry palm, penetration resistance, electrical conductivity 4 ms, and organic material content were as follows, and the results were very high.